Occupational Bullying among Employees at the University of Hama (Journal of Hama University, 2026)
The research aimed to identify the level of occupational bullying among workers at the University of Hama from their point of view, and to identify the differences between the average grades of the research sample members according to the research variables: (gender, type of work, years of experience, college). To achieve the research objectives, the researcher used the descriptive analytical method, designed a questionnaire consisting of (33) statements, and applied it to a sample consisting of (38) members of the educational staff and (41) employees in the Faculties of Education and Economics at the University of Hama, and used the statistical program (Spss-21) to process data.The search results showed the following:- The level of occupational bullying among employees at the University of Hama, from the employees’ point of view, was moderate.- There are statistically significant differences between the average responses of Hama University employees to the occupational bullying questionnaire attributed to gender, in favor of females.- There are no statistically significant differences between the average responses of Hama University employees to the occupational bullying questionnaire attributed to the variables: years of experience, college, and type of work.-In light of the research results, the researcher presented a set of proposals, the most important of which are: raising awareness by holding seminars and training courses for all employees, including academic staff, their assistants, and administrative staff at the university, about bullying in the workplace and ways to prevent it; promoting an ethical work environment at the Ministry of Higher Education and Scientific Research; continuing to develop regulations, laws, and rules that promote ethical behavior; combating bullying in all its forms among employees; and providing the best services to achieve a high level of performance.